Ignatius, harmonia viatoris - Bagüés Errondo, Jon (Boletín de la Real Sociedad Bascongada de Amigos del País, 2021)
State of the question in three aspects of music in relation to the figure of Saint Ignatius of Loyola and its projection. First of all, the contribution made by Félix Zabala about Ignatian music, or the refl ection of the saint’s fi gure in western musical creation, is summarised and updated. Secondly, the ancient sources of the melody used since the fi rst third of the nineteenth century are described as the March of Saint Ignatius, as well as the fi rst known recordings of the March. Thirdly, the paper reviews what the saint’s main biographers write about his personal relationship with music.